The Quaternary Biodiversity Crisis Assessed with Bulk Bone Metabarcoding - Seersholm, Frederik Valeur (Curtin University, 2020)
It is widely accepted that climate change and human activities have been central contributing factors in driving megafaunal extinctions but determining the exact contribution of each can be challenging to address. Using a novel genetic approach, Bulk Bone Metabarcoding, I explore the invisible genetic diversity in bone assemblages from across the globe. I show that human activities had a dramatic impact on the biodiversity in very different climates, from New Zealand over Texas to Greenland